Adoption of food safety practices in the informal milk processing units of Haryana, India – A value chain approach - Thakur, Amit; Dixit, Anil Kumar; Sharma, AK; Kumar, Shiv; Sendhil, R; Singh, AK (Indian Journal of Dairy Science, 2021)
In this paper, we analysed how the adoption level of food safety practices varies with milk procurement system in the informal milk processing sector and also developed a composite food safety index (FSI) deliberating the interplay of factors and actors. Primary data were collected from value chain actors, viz., small and micro dairy processing units (main actors), milk supplier, i.e., dairy farmer and milk vendors (upstream actors) and traders (downstream actors) in Karnal district of Haryana state of India. FSI of two identified milk procurement systems, viz., (i) own collection centres, and (ii) private vendors were compared. Processing units with own collection centres in production catchments have been able to establish better linkages with dairy upstream actors and resulted in better overall FSI (0.66) than those processing units procuring milk from private vendors (with FSI as 0.51). Further, the profitability of the processing unit is positively associated with the FSI, as consumers are willing to pay higher prices for safe milk. There was a need to design efficient milk procurement systems; design and development of efficient milk transport systems and processing technology along with training in post-milking handling for small vendors and processors for better food safety compliance in the milk value chain of the informal sector.Â